PERANCANGAN IGNITER UNTUK MOTOR ROKET PADAT RX 420/4000 - Sukandi Nasir Rohili (National Institute of Aeronautics and Space - LAPAN, 2006)
Igniter is a rocket component with the function of providing activated energy to the surface of solid propellant in the burning chamber of the rocket motor. Igniter design needs overall data of the rocket especially initial free volume and stable combustion pressure of the propellant. The properties of either primer or main charge especially its density and fraction of condensed particles of it combustion products are also needed. This paper presents the design of igniter for RX-420/4000 solid rocket with wagon wheel-cylinder dual configuration. The design result gives data as follows main case length = 302.6 mm, diameter = 52 mm; main charge weight of 338.31 g; volume = 212.19 cc and nozzle throat area = 12.6 mm; the intermediate case of 200 mm length; 30 mm diameter with black powder weight = 310.87 g and volume of 141.37 cc, the overall length of igniter included stick of 402.6 mm. Keywords: Igniter, Motor roket, RX 420/4000.